Ethnobotanical Study and Conservation Status of Plants Used by the Tigwahanon-Manobo in Mt. Malimumu, San Fernando, Bukidnon, Philippines: Ethnobotanical study and conservation status of plants used by the Tigwahanon-Manobo - Victor B Amoroso; Mark Lylod G. Dapar (Journal of Tropical Life Science, 2022)
Central Mindanao, Philippines, is a center of the cultural wealth of knowledge andbotanical resources in the southern archipelago. However, traditional plant resources remain unexplored, and most of the tribal communities remain undocumented. Manobo tribe is one of the most populated and diverse tribal communitiesin the country, including the secluded Tigwahanon-Manobo community in Mt.Malimumu, San Fernando, Bukidnon, Philippines. Hence, this study provides ethnobotanical information and conservation status of plants along a 1-km transectwalk in Mt. Malimumu used by the Tigwahanon-Manobo. A guided field walkwith the tribal chieftains and tribal healer documented a total of 23 species in 22genera belonging to 20 families, of which four species, namely Dillenia philippinensis Rolfe, Nepenthes cornuta Marwinski, Coritico, Wistuba, Micheler,Gronem., Gieray & V.B.Amoroso, Nepenthes truncata Macfarl., and Pandanusmindanaensis Martelli, are Philippine endemics. Three families, namely Nepenthaceae, Melastomataceae, and Rubiaceae, are the most represented with two species each. Based on the combined international (IUCN 2021) and national (DENRDAO 2017-11) listing of conservation status, one species was assessed as Critically Endangered (Aquilaria malaccensis Lam.) and another one as Endangered(N. truncata). Two species were assessed as Vulnerable (Agathis philippinensisWarb. and N. cornuta) and one species as Near Threatened (D. philippinensis).Six species were identified as Least Concern while the rest of the species were notyet evaluated. This participatory research provides the first ethnobotanical studyand conservation status of traditional plants used by Tigwahanon-Manobo for foodand medicine, as well as economic and ecological uses needing conservation andprotection of their natural resources.Keywords: Conservation, Ethnobotany, Food plants, Indigenous, Medicinalplants, Mindanao